THE EFFECT OF FREQUENCY AND PATTERN OF SAFETY COMMUNICATION ON SAFETY BEHAVIOR ON CONSTRUCTION PROJECTS IN SURABAYA - Dharmawan, Randy Karuna; Andi; Rahardjo, Jani (Program Studi Magister Teknik Sipil - Petra Christian University, 2025)
Construction project in Indonesia is one of the most significant contributors to the number of work accidents. Safety communication is generally a top priority in the field, considering that the construction industry is most prone to accidents and injuries. In this study, data were collected by distributing questionnaires to 39 working groups in the Surabaya construction industry, which aims to determine the effect of the frequency and pattern of safety communication on safety behavior, consisting of safety compliance and safety participation of workers in construction projects. The results showed that safety communication occurs once a week in a workgroup. The supervisor performs safety communication with 63.80% of all members in a workgroup. Meanwhile, the average value of safety compliance in all construction projects is considered relatively high, which is 3,582. This shows that construction workers are pretty obedient to the existing rules in construction projects. On the other hand, the average value of safety participation in the whole project is relatively low, which is 2.815. This shows that workers still do not know the importance of safety participation in construction projects. Safety communication and supervisory out-centrality positively and significantly impact safety compliance. In addition, supervisory out-centrality also completely and greatly influences safety participation.